The influence of entrepreneurial orientation and learning orientation on innovation performance of SMEs in Indonesia: Organizational learning as a mediator - Vigory Gloriman Manalu; Adi Santoso; Eman Sulaiman (Problems and Perspectives in Management)
SMEs are the backbone of the economy in various countries. SMEs are usually associated with their entrepreneurial capabilities and organizational culture to create sustainable innovation. This study aims to analyze the relationship between learning orientation and entrepreneurial orientation on SME innovation performance and examine the role of organizational learning as a mediator in this relationship. A quantitative approach was used. Data were collected through a survey of SME owners or managers from West Java who focused on the food and beverage, handicraft, and fashion industrial sectors. The questionnaire collection took place from August to November 2024. Two hundred thirty-seven questionnaires were retrieved for the analysis. The structural equation modeling (SEM) approach has been used to test the hypotheses. This study found a positive and significant relationship between learning orientation and organizational learning (p < 0.05, β= 0.54), entrepreneurial orientation and innovation performance (p < 0.05, β = 0.501), entrepreneurial orientation and organizational learning (p < 0.05, β = 0.5), and organizational orientation and innovation performance (p < 0.05, β = 0.446). In contrast, the relationship between learning orientation and innovation performance was insignificant (p > 0.05, β = 0.098). A good understanding of entrepreneurial orientation will allow SMEs to innovate better and survive amidst business competition. Learning orientation, which is considered to improve innovation performance, did not significantly influence SMEs in West Java. On the other hand, SMEs in West Java must improve their organizational learning, especially organizational culture related to shared vision, which is expected to influence innovation performance.